Performance analysis of packet length in multiple optical channels for local area network - Aznor Hanah, Abdul Halim; Ahmad, R. Badlishah, Prof. Dr.; Abid, Yahya; Norlydiana, Ramly; Kan, Phak Eh; Fazrul Faiz, Zakaria (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://www.ieee.org/index.html